2019
DOI: 10.3389/fpsyg.2019.00579
|View full text |Cite
|
Sign up to set email alerts
|

Appearance Teasing and Mental Health: Gender Differences and Mediation Effects of Appearance-Based Rejection Sensitivity and Dysmorphic Concerns

Abstract: Appearance teasing is a common phenomenon in social interactions, especially in adolescence. Several studies have shown its negative impact on mental health as well as on body image. While these findings prove stable in various contexts, less evidence is available for possible gender differences in these relationships. In particular, the role of two important body image variables – appearance-based rejection sensitivity (ARS) and dysmorphic concerns – and their contribution to mental health impairments has not… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
19
1
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 34 publications
(24 citation statements)
references
References 97 publications
(168 reference statements)
3
19
1
1
Order By: Relevance
“…These results highlight the prominent role in both childhood and adulthood of social experiences related to hair loss in shaping mental health outcomes among women. This finding also supports previous evidence linking childhood appearance-related teasing experiences with depression, anxiety, and low self-esteem in women [ 50 ]. Of interest, we found that women who were irradiated at a younger age experienced more mental health problems.…”
Section: Discussionsupporting
confidence: 91%
“…These results highlight the prominent role in both childhood and adulthood of social experiences related to hair loss in shaping mental health outcomes among women. This finding also supports previous evidence linking childhood appearance-related teasing experiences with depression, anxiety, and low self-esteem in women [ 50 ]. Of interest, we found that women who were irradiated at a younger age experienced more mental health problems.…”
Section: Discussionsupporting
confidence: 91%
“…Both were also more likely to report having experienced verbal bullying during their childhood. This finding is in line with a previous study based on a community sample that showed a similar frequency of appearance-related teasing experiences in childhood and adolescence between men and women [44].…”
Section: Discussionsupporting
confidence: 93%
“…Features of appearance anxiety include excessive appearance concerns and impairing, time-consuming behaviors, such as repetitive checking and excessive grooming to hide or camouflage flaws (Schmidt & Martin, 2019). In past research, appearance anxiety symptom measures have tended to assess offline behaviors, such as checking appearance in a mirror (Veale et al, 2013;Roberts et al 2018).…”
Section: Offline Appearance Anxiety and Online Appearance Preoccupationmentioning
confidence: 99%